Shear stress‐dependent targeting efficiency using self‐assembled gelatin–oleic nanoparticles in a biomimetic microfluidic system - Kang, Taehee; Park, Chulhun; Meghani, Nileshkumar; Tran, Thao T.D.; Tran, Phuong H.L.; Lee, Beom Jin (Pharmaceutics, 2020)
Cellular properties and microenvironments, as well as the characteristics of nanoparticles (NPs), affect the cellular uptake and cytotoxic effects of drug‐loaded NPs. Since there is fluid flow in the human blood system, fluid flow also affects the drug delivery efficiency of NPs. This study aimed to evaluate the cellular behaviors of drug‐loaded soft NPs on A549 cancer cells under different levels of shear stress (0.5, 5, and 50 dynes/cm2) in the biomimetic microfluidic system. The soft self‐assembled NPs were formed by the gelatin–oleic conjugate (GOC). The poorly watersoluble coumarin‐6 or paclitaxel (PTX) were used as model markers for encapsulation within selfassembled NPs (C‐GONs or PTX‐GONs, respectively). The cellular uptake of C‐GONs was found to be improved with shear‐stress dependence. The inhibitory concentration (IC50) of PTX‐GONs at 0.5, 5, and 50 dynes/cm2 was 0.106 μg/mL, 0.108 μg/mL, and 0.091 μg/mL, respectively, as compared to 0.138 μg/mL in a static condition. The cell killing efficiency of PTX‐GONs was increased in the highest shear stress of 50 dynes/cm2 in the static condition, and other levels of shear stress in dynamic conditions.
Keywords: Biomimetic shear stress; Cell dynamic environment; Cellular uptake; Coumarin‐6; Fattigation‐platform NPs; Gelatin–oleic conjugate; Inhibitory concentration; Paclitaxel; Self‐assembly